Exploring the challenges of implementing e-health: a protocol for an update of a systematic review of reviews. Issue 4 (13th April 2015) - Ross, Jamie; Stevenson, Fiona; Lau, Rosa; Murray, Elizabeth
Abstract : Introduction: There is great potential for e-health to deliver cost-effective, quality healthcare and spending on e-health systems by governments and healthcare systems is increasing worldwide. However, the literature often describes problematic and unsuccessful attempts to implement these new technologies into routine clinical practice. To understand and address the challenges of implementing e-health, a systematic review was conducted in 2009, which identified several conceptual barriers and facilitators to implementation. As technology is rapidly changing and new e-health solutions are constantly evolving to meet the needs of current practice, an update of this review is deemed necessary to understand current challenges to the implementation of e-health. This research aims to identify, summarise and synthesise currently available evidence, by undertaking a systematic review of reviews to explore the barriers and facilitators to implementing e-health across a range of healthcare settings. Methods and analysis: This is a protocol for an update of a systematic review of reviews. We will search MEDLINE, EMBASE, CINAHL, PSYCINFO and The Cochrane Library for studies published between 2009 and 2014. We will check reference lists of included studies for further studies. Two authors will independently screen the titles and abstracts identified from the search; any discrepancies will be resolved by discussion and consensus. Full-text papers will be obtained and relevant reviews will be selected against inclusion criteria. Eligible reviews have to be based on the implementation of e-health technologies. Data from eligible reviews will be extracted using a data abstraction form. A thematic analysis of barriers and facilitators to e-health implementation will be conducted. Ethics and dissemination: Ethical approval is not required. The permission of the original authors to update the review was sought and granted. Trial registration number: PROSPERO CRD42015017661.